Results of the Comparative Analysis of the Willingness-To-Pay Threshold Indicators for Introduction of Innovative Technologies in Healthcare Calculated on the Basis of the Purchasing Power Parity of the Population in Ukraine, Azerbaijan, Armenia, and Georgia - Hanna Panfilova (Journal of Global Pharma Technology, 2020)
Objective: To conduct a comparative analysis of the dynamics of changes in the willingness-to-pay indicators concerning introduction of the innovative technology in the national healthcare systems of Azerbaijan, Armenia, Georgia and Ukraine. Methods: The studies used the “Willingness-to-pay” calculation method proposed by the WHO Commission on Health Macroeconomics and Economics. Calculation and comparison of willingness-to-pay indicators in the reference countries was carried out on the basis of the purchasing power parity (PPP) of the population. Results: It was found that during 2010-2017 Azerbaijan consistently held the leading position when introducing the innovative technology in healthcare by the willingness-to-pay value. By the average value of willingness-to-pay indicators (in 2010-2017) the reference countries were distributed in ascending order of indicators in the following way: Armenia (24, 28 USD Thousand); Ukraine (25,02 USD Thousand); Georgia (26,30 USD Thousand); Azerbaijan (50,61 USD Thousand). Therefore, the average value of the willingness-to-pay indicator in Azerbaijan was approximately twice as much as in other reference countries. Іn ascending order of the average growth rate values (%) of the willingness-to-pay indicator the countries were distributed as follows: Azerbaijan (101.69%); Ukraine (102.02%); Armenia (105.4%); Georgia (107.2%). Azerbaijan demonstrated the highest willingness-to-pay indicators, but it showed the lowest average growth rates (%) within 2010-2017. The highest growth rate (%) of the willingness-to-pay indicator was observed in Georgia. Conclusion: The results of the studies conducted can be used to form an objective assessment of the threshold values of national healthcare systems in Azerbaijan, Armenia, Georgia and Ukraine. Keywords: Innovative drug, Innovative health technology, Health technology assessment, Pharmaceutical provision of the population, Willingness-to-pay indicator.